Spindle tubulin and MTOC asymmetries may explain meiotic drive in oocytes - Tianyu Wu (Nature Portfolio, 2018)
During ‘meiotic drive’, some chromosomes can bias their spindle orientation and thus be retained in the egg. Here, the authors find that this phenomenon can be driven by microtubule force asymmetry on chromosomes with differently sized centromeres and kinetochores.